Understanding risk : recent contributions from the journal of risk and governance (Economic issues, problems and perspectives series., 2013)
The book is divided into three sections. The first section examines issues in relation to corporate governance in the private sector, with emphasis being placed on issues such as 'Board Decision-Making;' 'Earnings Management and Audit Committee Effectiveness;' and 'Corporate Governance Failures.' These contributions are complemented by the second section, which looks at governance and risk issues affecting the public sector, with a focus being placed on 'Public-Private Sector Partnering' and the impact of regulatory reform on the life sciences. Section three focuses on societal risk management.